Blended collaborative care in the secondary prevention of coronary heart disease improves risk factor control: Results of a randomised feasibility study. (1st February 2020) - Bosselmann, Lena; Fangauf, Stella V; Herbeck Belnap, Birgit; Chavanon, Mira-Lynn; Nagel, Jonas; Neitzel, Claudia; Schertz, Anna; Hummers, Eva; Wachter, Rolf; Herrmann-Lingen, Christoph
Abstract: Background: Risk factor control is essential in limiting the progression of coronary heart disease, but the necessary active patient involvement is often difficult to realise, especially in patients suffering psychosocial risk factors (e.g. distress). Blended collaborative care has been shown as an effective treatment addition, in which a (non-physician) care manager supports patients in implementing and sustaining lifestyle changes, follows-up on patients, and integrates care across providers, targeting both, somatic and psychosocial risk factors. Aims: The aim of this study was to test the feasibility, acceptance and effect of a six-month blended collaborative care intervention in Germany. Methods: For our randomised controlled pilot study with a crossover design we recruited coronary heart disease patients with ⩾1 insufficiently controlled cardiac risk factors and randomised them to either immediate blended collaborative care intervention (immediate intervention group, n =20) or waiting control (waiting control group, n =20). Results: Participation rate in the intervention phase was 67% ( n =40), and participants reported high satisfaction ( M= 1.63, standard deviation=0.69; scale 1 (very high) to 5 (very low)). The number of risk factors decreased significantly from baseline to six months in the immediate intervention group ( t (60)=3.07, p =0.003), but not in the waiting control group t (60)=−0.29, p =0.77). Similarly, at the end of their intervention following the six-month waiting period, the waiting control group also showed a significant reduction of risk factors ( t (60)=3.88, p <0.001). Conclusion: This study shows that blended collaborative care can be a feasible, accepted and effective addition to standard medical care in the secondary prevention of coronary heart disease in the German healthcare system.